2017
DOI: 10.1177/1010539517709028
|View full text |Cite
|
Sign up to set email alerts
|

Differentials in Cardiovascular Risk Factors and Diabetes by Socioeconomic Status and Sex in Kalutara, Sri Lanka

Abstract: Since 1950, cardiovascular disease (CVD) has emerged as a leading cause of mortality in Sri Lanka, especially in men. In 2014, a survey in Kalutara to assess CVD and type 2 diabetes mellitus (T2DM) risk factors in adults aged 25 to 64 years (n = 1011), and associations with sex and socioeconomic status (SES), found similar CVD risk factors in both sexes, except for daily tobacco smoking at 19% in men and nil in women, and higher body mass index (BMI) in women than men. With increasing SES in men, there were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 16 publications
(30 reference statements)
1
23
0
Order By: Relevance
“…These differences in health behavior not only affect health status but also SES, and regular smoking and drinking behaviors cause negative effects on SES, especially income level [31]; hence, the difference in health behavior between and male and female workers was found to affect CVD-related health status according to SES. Examining the association between income and obesity or abdominal obesity, Gamlath et al [11] reported that as the income of workers in Sri Lanka increased, the WC and risk of developing obesity increased for male workers but decreased for female workers, aligning with the findings of this study. Due to work-related stress and unhealthy lifestyles, such as frequent drinking and smoking, male workers are more exposed to health risk factors than female workers [36].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These differences in health behavior not only affect health status but also SES, and regular smoking and drinking behaviors cause negative effects on SES, especially income level [31]; hence, the difference in health behavior between and male and female workers was found to affect CVD-related health status according to SES. Examining the association between income and obesity or abdominal obesity, Gamlath et al [11] reported that as the income of workers in Sri Lanka increased, the WC and risk of developing obesity increased for male workers but decreased for female workers, aligning with the findings of this study. Due to work-related stress and unhealthy lifestyles, such as frequent drinking and smoking, male workers are more exposed to health risk factors than female workers [36].…”
Section: Discussionsupporting
confidence: 86%
“…Socioeconomic status (SES) is reported to have a significant influence on the risk of cardiovascular diseases in adults [8][9][10][11]. SES affects the incidence of cardiovascular diseases through its effect on health status [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,19 Socioeconomic factors have been reported to impact the incidence of cardiovascular disease and the degrees of their effect on health status vary between males and females. 20,21 Numerous studies have examined the association between socioeconomic status and the cardiovascular disease-related health status and they showed income and education levels are associated with obesity and abdominal obesity. 21,22 Our findings support that individuals with lower income and education levels have higher rates of obesity and abdominal obesity, including especially in females.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Numerous studies have examined the association between socioeconomic status and the cardiovascular disease-related health status and they showed income and education levels are associated with obesity and abdominal obesity. 21,22 Our findings support that individuals with lower income and education levels have higher rates of obesity and abdominal obesity, including especially in females. Similar to our findings, a study using data from the NHIS database identified a sex difference in the prevalence and odds ratio of obesity and abdominal obesity in workers: those with a lower income or rural residence were correlated with obesity and abdominal obesity among female workers.…”
Section: Discussionmentioning
confidence: 99%